Ecological studies of aphid (Aphis gossypii Glover), vector of virus disease of chilli (Capsicum annuum L.) and its predators / Fairuz Khalid - Khalid, Fairuz (2007)
Studies were conducted to determine the seasonal trends of the cotton aphid Aphis gossypii Glover (Homoptera: Aphididae), its natural enemies (Coccinellidae, Chrysopidae and Araneae) and virus disease incidences on chilli variety MC4 in seven cropping periods. Sampling of alate A. gossypii was done using yellow pan trap while the apterous, natural enemies and virus disease incidence were counted in situ. The spatial distribution of arthropods within each cropping period was analyzed using variance-to-mean ratio, Morisita's Index and Lloyd Index of Patchiness model. The spatial distribution of arthropods between cropping periods was analyzed using Taylor's Power Law and Patchiness Regression model while virus incidences were analyzed using logistic model. Results of the study showed that apterous aphids were found in abundance at the bottom stratum. The populations of apterous aphids on chilli were found to be low in the first 4 cropping periods but high in the fifth, sixth and seventh cropping period. Alate aphid population were found significantly higher in the early mornir'f1, 0800 and 1000 hr and significantly lower in the evening, 1400 and 1600 hr. The population of natural enemies, coccinellidae, chrysopidae and araneae were found low throughout the seven cropping period where the coccinellidae, chrysopidae and araneae preferred the upper, bottom and middle stratum, respectively. Generally, the cumulative data showed a sigmoidal trends. The vertical distribution of apterous A. gossypii and its natural enemies seems to be influenced with climatic condition and phenology of chilli plant along the vertical gradient of chilli plants. Analysis of virus disease incidence showed a slow development of virus disease during the early and late growth period while rapid development was observed in the middle growth period of each cropping. The fifth cropping period demonstrated the most rapid development of virus infection compared to other cropping periods. The Vin IS Apparent Infection Rate (VAIR) analysis revealed that average increasing rate of virus disease in all cropping periods was from 0.077 to 0.32 unit. The analysis also revealed that, the disease took 46.9 to 67.0 days to spread 50% in all cropping periods and 50.2 to 70.1 days to infect 90% of the plot. The Area Under Disease Progress Curve (AUDPC) analysis showed that the chilli plant was highly infected with viruses in the flowering stage followed by fruiting stage. The within field spatial distribution of virus count data were illustrated by the 'red-blue' plots which were analyzed using SADiE (Spatial Analysis by Distance Indices), showed a ephemeral spatial pattern of virus incidences in each sampling date of every cropping periods.